The Percutaneous shunting in Lower Urinary Tract Obstruction (PLUTO) study and randomised controlled trial : evaluation of the effectiveness, cost-effectiveness and acceptability of percutaneous vesicoamniotic shunting for lower urinary tract obstruction /: evaluation of the effectiveness, cost-effectiveness and acceptability of percutaneous vesicoamniotic shunting for lower urinary tract obstruction. (December 2013) - Morris, R. K (R. Katie)
No abstract available